Beyond environmental factors: What retail investors want from esg investing - Sara Fadavi; Jakob Famulok; Christine Laudenbach; Vincent Lindner (Leibniz Institute for Financial Research SAFE, 2025)
The reform of the EU's sustainable finance framework, in particular the Sustainable Finance Disclosure Regulation (SFDR), reopens a debate about ESG labels and their alignment with investor preferences and policy objectives. This paper provides novel evidence on the role of ESG exclusion criteria in retail investment decisions. Using survey and experimental data from 1,174 German retail investors, we show that exclusion-based preferences are central to how investors interpret and use ESG labels. Investors place significantly greater weight on social and governance exclusions than on environmental ones (S > G > E), with human rights, animal welfare, and corruption emerging as dominant concerns. Experimental evidence further demonstrates that only investors with strong altruistic values adjust their portfolios when provided with granular ESG information. Consequently, reforms to the sustainable framework should acknowledge the importance of social and governance exclusions and move towards granular labels, while being aware of the limits of sustainability labelling on the green transition.
Keywords: 330; ESG Exclusion Criteria; Retail Investor Preferences; Sustainable Finance Regulation (SFDR)